Physiological potential of cucumber melon seeds subjected to salinity (Research, Society and Development, 2020)
The cultivation of melon is one of the main agricultural activities in Northeast Brazil, adapting well to the environmental conditions of the region. Local varieties, also called creoles, are widely used in domestic consumption, including cucumber melons. However, one of the limiting factors for agricultural production in the region is the salinity of the soils and water used for irrigation, directly interfering with the germination process of the seeds. In this context, the objective was to evaluate the influence of salinity on the germination and evolution of the imbibition process of cucumber melon seeds. The experiment was conducted in a completely randomized design with five electrical conductivities of irrigation water (ECw = 0.0; 0.5; 1.5; 3.5 and 4.5 dS m-1), with four replications of 50 seeds. The seed water absorption and increment curve and the percentage, first count, average speed index, average time, average speed and relative germination frequency were evaluated. The data were submitted to analysis of variance and, in cases of significance, regression analysis. The cucumber melon is tolerant to salinity, but the vigor of the seeds is reduced with the increase of CEa. The water absorption lasts for 41 hours and the increment of 0.013 g of water per seed until root protrusion begins. In the evolution of the imbibition of the seeds, an extension of the duration of the process was observed with the increase of the saline concentrations.